Socioecological drivers of burnout – a mixed methods study of military health providers - Olapeju, Bolanle; Dong, Ting; Soh, Michael; Mushtaq, Omar; Chang, Hanna; Riegleman, David; Hemmer, Paul A.; Schwab, Stephen D.; Shanahan, Patrice; Johnson-Boua, Kimberly; Durning, Steven J. (Frontiers in Public Health, 2024)
IntroductionHealth provider burnout is highly prevalent (28–51%) in the US and may contribute to a projected national health provider shortage by 2030. The Socioecological Model (SEM) is a proven conceptual framework used to identify influencing factors and design relevant solutions to improve health outcomes across multiple ecological levels. This study applied the SEM to identify modifiable drivers and solutions of burnout across multiple levels among US Military health providers.MethodsWe conducted a cross-sectional mixed methods study using an online survey (N = 129) and in-depth interviews (N = 25) of active duty military health providers. Our primary quantitative outcome was self-reported definite, unrelenting, or complete burnout. Our quantitative analysis included chi-square tests of association and bootstrapped multivariable logistic regressions to explore SEM-informed correlates of burnout, controlling for contextual variables. Our qualitative data explored providers individual experience with workplace stress and burnout, providing details on factors influencing burnout at the individual, interpersonal, organizational and military levels. The qualitative data was systematically coded and analyzed using grounded theory.ResultsAbout two-thirds (63%) of surveyed providers self-reported burnout. Individual-level factors significantly associated with burnout included a positive coping style (AOR = 0.21; 95% CI: 0.08–0.56), perceived control over workload (AOR = 0.17; 95% CI: 0.04–0.66), and satisfaction with the current job (AOR = 0.11; 95% CI: 0.03–0.39). At the organizational level, providers described as overworked (AOR = 10.58; 95% CI: 3.30–33.91) or in hectic or chaotic primary work areas (AOR = 7.54; 95% CI: 2.33–24.38) had higher rates of burnout. At the military level, providers who were happy with their career path and promotion plan (AOR = 0.16; 95% CI: 0.06–0.44) reported lower rates of burnout. The organizational level had the highest cumulative impact of modifiable factors on burnout (AOR: 0.15; 95% CI: 0.06, 0.36). Qualitative interviews corroborated survey findings and highlighted the individual level manifestations of burnout, the role of interpersonal support as mitigators of burnout and the complexity of governmental and military policies impacting provider wellness.DiscussionIdentified factors influencing burnout at various levels may inform potential data-driven interventions to ensure a functional and vibrant US Military health. Data-driven strategies may include opportunities to balance work demands with resources and ability to cope as well as improve positive coping skills, attitudes and experiences related to work.